Instagram as a Media for Reproductive Health Education In Young Women - Susilowati, Yuanita Ani; Utami, Yohana Putri; Sinaga, Friska; Setyarini, Elizabeth Ari (Universitas Negeri Gorontalo, 2024)
The Indonesian Demographic Health Survey for Adolescent Reproductive Health in 2017 shows that there are still various health problems including low levels of knowledge related to unwanted pregna ncies, abortions and sexually transmitted infections. Knowledge of reproductive health is important for adolescents to deal with various physical and psychological changes they experience and prevent problems due to negligence in reproductive health. The research objective was to determine the effectiveness of health education through Instagram in increasing adolescent knowledge about reproductive health. This study is a pre-experimental research with one group pretest posttest design. The number of samples used were 50 female adolescene using Instagram. Sample is selected using purposive sampling technique. Data were collected using a questionnaire with a guttman scale and analyzed using the Wilcoxon signed rank test. The statistical test results obtained a p- value of 0.000 (p